2019
DOI: 10.7759/cureus.5353
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid Cyst in the Lumbar Paravertebral Muscle: A Case Report

Abstract: A hydatid cyst is a zoonotic disease caused by the worm Echinococcus granulosus. In endemic regions, it is a well-known differential diagnosis of cystic lesions, especially in the liver, lungs, brain, and vertebral column. Primary paravertebral muscle involvement, however, is rarely reported. In the current report, we present the case of an 11-year-old girl complaining of back pain with a well-defined single cystic lesion in her lumbar paravertebral multifidus muscle evident in imaging studies. The patient had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In this regard, a meta-analysis by Khalkhali et al on the prevalence of hydatid cysts in Iran found that although the rate of infection with hydatid cysts was higher in females than males, the difference was not statistically significant [6]. Thus, in some areas, a greater frequency of CE in males may be seen [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a meta-analysis by Khalkhali et al on the prevalence of hydatid cysts in Iran found that although the rate of infection with hydatid cysts was higher in females than males, the difference was not statistically significant [6]. Thus, in some areas, a greater frequency of CE in males may be seen [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The contractile nature of the muscles and the high lactic acid content make muscles not a suitable site for implantation of hydatid cysts 3 . Among various muscle groups too, paraspinal muscles are much more rarely affected 7,8 …”
Section: Discussionmentioning
confidence: 99%
“…Hydatid cyst of muscle usually presents as a painless, slow‐growing, asymptomatic mass with a normal overlying skin, similar to our case presented above. A high index of suspicion is therefore necessary as its differential diagnosis can range from chronic hematoma and lipoma to malignant soft tissue tumors such as myxoid liposarcoma 7–9 . The diagnosis of hydatid cysts is initially sought with serology and imaging findings 10–12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies conducted by Cohen et al (1998) and Qaqish et al (2003) such associations were not observed [17,18]. Thus, in some areas, based on the culture and social criteria, men may cover the highest rate of CE infection [19][20][21].…”
Section: Discussionmentioning
confidence: 99%